Low‐complexity 2D central DOA estimation of coherently distributed sources with cross‐correlation matrix. Issue 16 (1st July 2014) - Yang, Xuemin; Li, Guangjun; Zheng, Zhi; Zhong, Lang
Abstract : A low‐complexity estimator for two‐dimensional (2D) central direction‐of‐arrival (DOA) estimation of multiple coherently distributed sources is proposed, which is based on applying the singular value decomposition method to the cross‐correlation matrix of the received signals at double parallel uniform linear arrays. The proposed estimator is performed with automatic parameter pairing. Simulation results confirm the efficacy of the proposed estimator.